RELATIONSHIP OF SERVICE DELIVERY WITH CUSTOMER LOYALTY IN RELIGIOUS TOURISM SERVICES (Study on Umrah Maktour Services in Bandung) - Kurniawan, Ryan (CENTRAL ASIA AND THE CAUCASUS, 2022)
The ability to provide the best service to customers is the most important thing that must be owned by the company so that the company's main goals can be achieved. The provision of good service is a service provided in accordance with the wishes and needs of the passengers themselves. Companies that provide services as promised will lead to a willingness from customers to repurchase the company concerned.I conducted this research entitled The Relationship between Service Delivery and Customer Loyalty at Maktour Bandung(Umrah) Travel, and the independent variable is service delivery and the dependent variable is customer loyalty. The purpose of this study is to analyze customer responses to service delivery. To analyze customer loyalty and to analyze the relationship between travel service delivery and customer loyalty at Maktour Bandung(Umrah). The research method used is the explanatory method which is useful for explaining the causal relationship between variables through hypothesis testing with data collection techniques through interviews and questionnaires with a sample of 111 people from a population of 125.The results showed that simultaneously tangible, empathy, reliability, responsiveness, and assurance together have a significant relationship. While partially the results of this study indicate that the sub-variables where responsiveness and empathy have a weak relationship with customer loyalty. This is different from the research conducted by Lo Liang Kheng et.all where the sub-variable reliability did not show an effect, while responsiveness showed similarity, that is, it had no effect, while in this study it had a weak relationship. Customer loyalty at Maktour Bandung(Umrah) as a whole has an average value of 3.88 which means it is high because it is in the interval 3.40 - 4.19. This shows that consumers are satisfied with the delivery of services provided by PT Dago Wisata Internasional.